Current Topics in Echinococcosis 2015
DOI: 10.5772/60820
|View full text |Cite
|
Sign up to set email alerts
|

Brain Hydatid Cyst

Abstract: Brain echinococcosis is the most common brain parasitic infection in the world. It happens in a very rare location, representing 1% to 2% all cases with hydatid disease. It is more common by approximately 50-70% in pediatric population and young adultswith a male predominance. The definite hosts of echinococcus are various carnivores; man is an accidental host. The growth of hydatid cysts is usually slow and asymptomatic, and clinical manifestations are caused by compression of the involved organ. CT provides … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 13 publications
(18 reference statements)
0
7
1
Order By: Relevance
“…In our study, the patient was a female child, but in the literature, male predominance was found (i.e. 50%-70%) [5]. The most common site in the brain is the parietal lobe [5].…”
Section: Plain Language Summarycontrasting
confidence: 46%
See 3 more Smart Citations
“…In our study, the patient was a female child, but in the literature, male predominance was found (i.e. 50%-70%) [5]. The most common site in the brain is the parietal lobe [5].…”
Section: Plain Language Summarycontrasting
confidence: 46%
“…Primary cysts are most of the times solitary and fertile, but secondary cysts are generally multiple and infertile [4,5]. The proposed mechanisms for the development of primary brain hydatid cyst are defective immune system within the brain parenchyma, the presence of cardiac anomalies like patent ductus arteriosus, and patent foramen ovale.…”
Section: Plain Language Summarymentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the collaboration with the infectious medicine specialist and neurosurgeons was key in excluding a possible infective cause. One of the most common causes of cystic lesions is zoonosis due to Echinococcus multilocularis which is found in the brain in 30% of cases [13]. Due to a slow growth of the hydatid cysts, the symptoms appear when they reach remarkable dimensions.…”
Section: Discussionmentioning
confidence: 99%